1992
DOI: 10.1180/minmag.1992.056.383.08
|View full text |Cite
|
Sign up to set email alerts
|

The stabilities of secondary tin minerals: abhurite and its relationships to Sn(II) and Sn(IV) oxides and oxyhydroxides

Abstract: The true formula of abhurite is Sn21Cllr(OH)140 6. A stability constant for the phase has been determined at 298.2 K. For the reaction Sn21CI16(OH)1406 (s) + 26H + (aq) ,~ 21Sn ~+ (aq) + 16CI-(aq) + 20H20 (1), log KH+ (298.2 K) is equal to -39.9 (7). This value is used to assess the relative stability of abhurite in the natural environment and to evaluate its modes of occurrence in relation to other secondary Sn(II) and Sn(IV) species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…The absence of cassiterite cannot be explained thermodynamically, and therefore may be a result of sluggish kinetics. The stability of tin oxides and dissolved tin species was discussed by Edwards et al (1992) and Séby et al (2001). The Eh-pH conditions present in seawater and marine sediments fall within the stability field of cassiterite at a dissolved tin activity of 10 -10 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of cassiterite cannot be explained thermodynamically, and therefore may be a result of sluggish kinetics. The stability of tin oxides and dissolved tin species was discussed by Edwards et al (1992) and Séby et al (2001). The Eh-pH conditions present in seawater and marine sediments fall within the stability field of cassiterite at a dissolved tin activity of 10 -10 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolysis of tin ions has been well‐studied due to the relative importance of this metal to pre‐industrial and industrial societies . The work of Ditte provided the fundamental understanding of tin hydrolysis behavior, yet discrepancies found when reproducing this work and interpreting the resulting data, as explained by Bury and Partington, highlight the difficulty in handling tin oxides and hydroxychlorides.…”
Section: Introductionmentioning
confidence: 99%
“…Langer and Bogucki demonstrated that chelation of stannous ions with ethylenediamine tetraacetic acid stabilized the inorganic species with respect to hydrolysis chemistry, but this allowed for the more facile oxidation mechanism to dominate the solution and form stannic, tin (IV), complexes . Edwards et al further investigated the hydrolysis of stannous chloride (SnCl 2 ) as a function of pH in order to better quantify the stability of transient secondary tin minerals . These references give a good understanding of the complicated hydrolysis and complexation schemes of tin, yet the low solubility of tin compounds and complexes at pH values greater than 4 has limited the understanding of these schemes and highlights the need for additional techniques to characterize tin hydrolysis mechanisms within neutral and alkaline mixtures …”
Section: Introductionmentioning
confidence: 99%
“…Already in 1882, Ditte reported the formation of two different compounds precipitating depending on the amount of base added [7]. After decades of intensive research and many speculations about the composition and chemical nature [8], von Schnering et al published the crystal structure of the so-called basic tin(II) chloride with the chemical formula Sn II 21 O 6 (OH) 14 Cl 16 [9]. Later, the mineral abhurite was connected with this chemical compound [10].…”
Section: Introductionmentioning
confidence: 99%
“…The stability range of abhurite and its transition to hydroromarchite depending on the pH value has been discussed [13]. Edwars et al [8] 2013, Chen and Grandbois [15] reported in situ Raman spectroscopic investigations of the sequential hydrolysis of tin(II) chloride to abhurite, hydroromarchite and finally to romarchite, Sn II O. Their research demonstrates the formation of abhurite from a tin(II) chloride solution by adding a sodium hydroxide solution.…”
Section: Introductionmentioning
confidence: 99%